The Challenges of Supporting Young Children’s Outdoor Play in Early Childhood Education and Care Settings - Ji Hyun Oh (Northwest Journal of Teacher Education, 2023)
This study explored preschool teachers’ beliefs about the challenges they have experienced when supporting young children’s outdoor play. Through Charmaz’s (2006) constructivist grounded theory data analysis process, two types of challenges for providing outdoor play were specified including: (1) natural environmental challenges, such as insect bites, allergies, and severe weather issues and (2) physical environmental challenges that include lack of play materials/environments and playground maintenance. The participant teachers perceive that these challenges are related to their preparation and planning for outdoor play including the provision of outdoor play, allotted play time, and a number of outdoor learning activities.